WFDC21P is essential for G3BP1-mediated RIG-I activation and antitumor immunity in triple-negative breast cancer - Zean Li; Yi Wang; Zhengjie Chen; Renzhong Liu; Zheng-Hao Lai; Na-Na Li; Yiming Zhao; Yue Wang; Man-Li Luo (Proceedings of the National Academy of Sciences, 2026)
Deciphering the mechanisms underlying antitumor immunity is critical for improving cancer immunotherapy efficacy. Here, we identify WFDC21P (lnc-DC) as a positive regulator of antitumor immunity through promoting the activation of the RNA-sensing retinoic acid-inducible gene-I (RIG-I) pathway in triple-negative breast cancer (TNBC). WFDC21P directly binds to RIG-I-interacting protein G3BP1 and is required for a rapid assembly of functional G3BP1-RIG-I-double-stranded RNAs condensates via phase separation, which enables robust activation of RIG-I. WFDC21P is downregulated in TNBC tissues and correlates with less CD8 + T cell infiltration in tumors and worse outcome of patients. WFDC21P knockdown in TNBC cells markedly dampens RIG-I activation and reduces the expression of IFN-stimulated genes, including MHC-I and PD-L1. In syngeneic tumor models, WFDC21P expression not only suppresses tumor growth by augmenting the infiltration and cytotoxic function of CD8 + T cells but also improves the response to immune checkpoint blockade, thus providing a compelling combination immunotherapy strategy for treating triple-negative breast cancer.